Interoception and the uneasiness of the mind: affect as perceptual style - Petersen, Sibylle; Von Leupoldt, Andreas; Van Den Bergh, Omer (Frontiers in Psychology, 2015)
Autonomous system models of interoception describe perception as an active process in which the brain generates and tests hypotheses about the body on the basis of proximal information. This view of perception as inference allows a new perspective on the role of affect in perception. Affect and interoception are closely linked, but processes underlying this link are poorly understood. We suggest that a predictive coding perspective allows acknowledging affect as integral part of information processing. We outline how affect may intrinsically modify processes of interoception by acting as threshold mechanism in stimulus grouping and information compression. We outline how well-established methods, for example, from categorization research may allow quantifying this influence of affect on perception in empirical tests of predictive coding models. We discuss how this may enrich the study of the relationship between affect and interoception and may have important clinical relevance.